Surveying workers perceptions in the automotive industry - a preventive tool for monitoring OSH measures - Neag Nicoleta Paula; Gaureanu Alin; Calciu Nicoleta-Lavinia; Tamasila Matei (MATEC Web of Conferences, 2021)
In an efficient OSH management system, it is necessary to approach continuous improvement, being recommended the PDCA system (Plan Do Check Act). In Romania, there is well-developed legislation, who establishes measures and actions in the field of OSH. The companies comply by creating an implementation plan, but most of them remain at this stage, without verifying the degree of implementation, with adaptation/updating of the measures. In this paper, we highlight some reference elements that can be periodically probed, so that the OSH management system can have a prompt and justified improvement reaction. The mode of obtaining this information regarding the implemented measures can be achieved through a periodic questionnaire that diagnoses two relevant aspects: 1. workers’ perceptions - which assess the implementation method; 2. the consequences/accidents - that assess the efficiency of the measures and their application/implementation. The two key elements (perception and consequences) will be used by the questionnaire responding workers after the implementation stage. The profile of these respondents is considered, and depending on their age, function, and level of education, the new applicable measures can be dimensioned. Only through continuous, monitored, and adapted improvement can the most effective measures be implemented, so that prevention fulfils its fundamental purpose, to contribute to the predictability and sustainability of an efficient automotive enterprise.